Tailored Skin Flaps for Hand Reconstruction. Issue 9 (30th September 2022) - Vizcay, Macarena; Pajardi, Giorgio Eugenio; Zanchetta, Francesco; Stucchi, Sara; Baez, Antonio; Troisi, Luigi
Abstract : Introduction: Acquired soft-tissue defects of the hand can be a result of different types of trauma, infection, tumor resection, or burns. The evolution of the design and types of flaps have optimized the reconstruction and, nowadays, it is important to achieve not only a functional result but also an aesthetic result. The aim of the present study is to propose a model for treating a wide variety of skin defects in the hands based on our flap experience. Methods: We conducted a retrospective study from February 2019 to January 2022, which included all patients who underwent a skin flap for hand reconstruction. Patients' medical records were reviewed and data collected included demographics, smoking status, presence of risk factors, type of trauma, flap reconstruction, dimensions, reoperations, and long-term complications. Results: A total of 99 patients underwent skin flap-based reconstruction for hand trauma between February 2019 until January 2022. The mean age was 43.9 (range 38.3–49.5), 87.9% of patients were male, and follow-up was between 2 and 30 months; 90.9% of the flaps were free flaps, and the rest were pedicle flaps (3% of them being propeller flaps). Conclusions: When planning a hand reconstruction, it is vital to ensure that the outcomes are not only functional but also aesthetic, with minimum donor site morbidity; in this study, we showed a variety of flaps that can be applied to achieve this goal. We believe that the final decision should be made after comprehending the defect and the patient's preferences.